Psychopathy, expert testimony, and indeterminate sentences: exploring the relationship between Psychopathy Checklist-Revised testimony and trial outcome in Canada - Lloyd, Caleb D. (Legal and criminological psychology, 2010)
Purpose. Psychopathy, as measured by the Hare Psychopathy Checklist-Revised (PCL-R), has the potential to inform judges attempting to preventatively detain Canada's highest risk offenders. However, studies examining the stigma of the psychopathy label give reason to exercise caution when expert witnesses introduce PCL-R scores into their testimony. Methods. Judges' written or oral judgments were gathered from a publically available database in Canada. Dangerous offender hearings (N = 136) were examined to determine how factors within expert witness testimony were related to sentences of indeterminate or determinate length. Results. Results show a trend for PCL-R scores to be related to trial outcome. Specifically, psychopathy diagnoses were correlated to experts' ratings of treatment amenability which were in turn related to trial outcome. In addition, experts tended to show partisan allegiance in the way they scored offenders on the PCL-R. Conclusion. Discussion advocates a measure of caution when using PCL-R testimony in an adversarial court context. Further research clarifying the role psychopathy plays in court decisions is also encouraged.